Gas dispersion risk analysis of safety gap effect on the innovating FLNG vessel with a cylindrical platform - Li, Jingde; Ma, G.; Abdel-jawad, M.; Huang, Y. (Elsevier, 2016)
© 2016 Elsevier Ltd. While the effect of the safety gap on explosions is well known, little has been carried out to evaluate the effect of the safety gap on dispersion of gas releases, this paper evaluates the effect of safety gap on gas dispersion for a cylindrical Floating Liquefied Natural Gas (FLNG) vessel. The realistic ship-shaped and circular FLNG platforms are established and used for the detailed CFD based analysis; rather than the structural and hydrodynamics advantages of mobility, stability and cost efficiency etc., this study aims to investigate the safety of gas dispersion on the cylindrical FLNG and compare the safety gap effects on different configurations. A series of different safety gap configurations are evaluated for gas dispersion occurring in near field for the traditional FLNG while both near field and far field gas dispersion simulations are conducted on the cylindrical one. The overall results indicate that the safety gap is effective in reducing the gas cloud size in both FLNG configurations, however, when it comes to the gas dispersion in the far field against the leakage point, the safety gap increases the gas cloud size in the cylindrical FLNG vessel on the contrary.